Edukasi Kesehatan tentang Tanda Bahaya HIV/AIDS pada Ibu Hamil di Kepulauan Kamarian tahun 2023 - Windatania Mayasari; Sumirda Rahareng; Andi Herliah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Human Immunodeficiency Virus and AIDS (Aquired Immunodeficiency Syndrom) are infections diseases that are classified as one of the causes of maternal and child mortality. The purpose of community service activities is to provide health education to mothers abaout danger signs of HIV/AIDS. The method used lecture. The target for the activity is pregnant women in kamarian islands. Based on the results of these activities is an increase in the knowledge of pregnant woman in the kamarian islands.